2001
DOI: 10.1034/j.1600-0854.2001.21006.x
|View full text |Cite
|
Sign up to set email alerts
|

Actin Microfilaments Facilitate the Retrograde Transport from the Golgi Complex to the Endoplasmic Reticulum in Mammalian Cells

Abstract: The morphology and subcellular positioning of the Golgi complex depend on both microtubule and actin cytoskeletons. In contrast to microtubules, the role of actin cytoskeleton in the secretory pathway in mammalian cells has not been clearly established. Using cytochalasin D, we have previously shown that microfilaments are not involved in the endoplasmic reticulum-Golgi membrane dynamics. However, it has been reported that, unlike botulinum C2 toxin and latrunculins, cytochalasin D does not produce net depolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 35 publications
5
87
1
Order By: Relevance
“…Depolymerization of actin filaments and the subsequent osmotic swelling may also increase membrane tension in the Golgi complex [Morris and Homann, 2001;Sheetz, 2001] and thus decrease the reported differences in tension between the ER and Golgi [Upadhyaya and Sheetz, 2004] slowing down Golgi-to-ER membrane flow. Consistent with this hypothesis is the observation that LtB and C2 toxin treatments reduce the rate of the Golgi disassembly induced by brefeldin A [Valderrama et al, 2001]. Secondly, cisternae swelling could be also generated by the functional uncoupling of actin filaments with ion exchangers and/or vacuolar H þ -ATPases ((V)H þ -ATPases).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Depolymerization of actin filaments and the subsequent osmotic swelling may also increase membrane tension in the Golgi complex [Morris and Homann, 2001;Sheetz, 2001] and thus decrease the reported differences in tension between the ER and Golgi [Upadhyaya and Sheetz, 2004] slowing down Golgi-to-ER membrane flow. Consistent with this hypothesis is the observation that LtB and C2 toxin treatments reduce the rate of the Golgi disassembly induced by brefeldin A [Valderrama et al, 2001]. Secondly, cisternae swelling could be also generated by the functional uncoupling of actin filaments with ion exchangers and/or vacuolar H þ -ATPases ((V)H þ -ATPases).…”
Section: Discussionmentioning
confidence: 75%
“…We have previously reported that the disruption of actin filaments causes compaction of the Golgi complex in NRK cells [Valderrama et al, 1998[Valderrama et al, , 2001. However, it is not known (i) whether this unusual Golgi morphology is generated in other mammalian cell lines when the actin cytoskeleton is disrupted by actin toxins and (ii) whether different toxins cause equivalent alterations of Golgi ultrastructure.…”
Section: All Anti-actin Agents Induce Compaction Of the Golgi Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminal part (C2IN) of C2I, which interacts with the binding component C2II, was fused to full length C3lim or C3stau respectively (Haug et al 2006;Barth et al 1998). All mammalian cells studied so far are sensitive towards the C2-C3 fusion toxin (e.g., CHO, Hela and NIH-3T3 cells; Valderrama et al 2001;Wahl et al 2000;Meyer et al 2000;Vischer et al 2000).…”
Section: C3 Toxins Are Pharmacological Toolsmentioning
confidence: 99%